Uso de alfarina (Medicago sativa) en la alimentación de cobayos (Cavia porcellus) - Quijije Rade, Andrea Maitee (2025)
The objective of this study was to evaluate the effect of different levels of alfalfa meal (Medicago sativa) in fattening diets for guinea pigs (Cavia porcellus). A completely randomized design was used with 96 male guinea pigs, 21 days old and with an initial weight of 450 g, distributed into four treatments: T0 (no alfalfa meal), T1 (5%), T2 (10%), and T3 (15%), with six observational units per treatment. The bromatological analysis of alfalfa meal showed high levels of dry matter (90.95%), protein (17.4%), and fiber (21.67%). Regarding productive results, no significant differences (p>0.05) were found in weight gain, feed intake, or carcass yield. The highest weight was recorded in T1 (485 ± 100.26 g), while the lowest was in T0 (445 ± 52.32 g). T1 also showed the best feed conversion ratio (1.82 ± 0.09), whereas T3 had the highest (2.11 ± 0.08). Significant differences (p<0.05) were observed in mortality rates, with T1 showing the highest rate (8.33 ± 2.08%), compared to equivalent values in T0, T2, and T3 (4.17 ± 2.08%). In terms of cost-benefit ratio, significant differences (p<0.05) were found. T0 was the most profitable treatment, yielding the highest revenue ($296.64), lowest expenses ($154.39), greatest profit ($142.25), and the best cost-benefit index (0.92). It is concluded that the inclusion of alfalfa meal improves productive parameters at varying proportions in fattening diets for guinea pigs.